2022
DOI: 10.1094/phyto-03-22-0070-r
|View full text |Cite
|
Sign up to set email alerts
|

Fungicide Resistance and Host Influence on Population Structure in Botrytis spp. from Specialty Crops in California

Abstract: Botrytis is an important genus of plant pathogens causing pre- and post- harvest disease on diverse crops worldwide. This study evaluated Botrytis isolates collected from strawberry, blueberry, and table grape berries in California. Isolates were evaluated for resistance to eight different fungicides, and 60 amplicon markers were sequenced (neutral, species-identification, and fungicide-resistance associated) distributed across 15 of the 18 B. cinerea chromosomes. Fungicide resistance was common among the popu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 77 publications
0
2
0
Order By: Relevance
“…Thus, in the current study, we documented a further increase in MLR frequencies within the fungal population. Multiple resistance to fungicides in B. cinerea is a rapidly expanding problem in the fungal populations worldwide, reported in several studies during the last decade ( Leroch et al., 2011 ; de Miccolis Angelini et al., 2014 ; Fernandez-Ortuno et al., 2014 ; Li et al., 2014 ; Lu et al., 2016 ; Campia et al., 2017 ; Rupp et al., 2017 ; Cosseboom et al., 2020 ; Makris et al., 2022 ; Naegele et al., 2022 ). The observed increased frequencies of MLR strains in populations from crops heavily treated with fungicides are obviously associated with the high number of sprays required to successfully control the disease, the application of pre-packed mixtures of different active ingredients that are of high risk for resistance development, or the absence of effective alternative control methods that could contribute to a reduction of selection pressure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, in the current study, we documented a further increase in MLR frequencies within the fungal population. Multiple resistance to fungicides in B. cinerea is a rapidly expanding problem in the fungal populations worldwide, reported in several studies during the last decade ( Leroch et al., 2011 ; de Miccolis Angelini et al., 2014 ; Fernandez-Ortuno et al., 2014 ; Li et al., 2014 ; Lu et al., 2016 ; Campia et al., 2017 ; Rupp et al., 2017 ; Cosseboom et al., 2020 ; Makris et al., 2022 ; Naegele et al., 2022 ). The observed increased frequencies of MLR strains in populations from crops heavily treated with fungicides are obviously associated with the high number of sprays required to successfully control the disease, the application of pre-packed mixtures of different active ingredients that are of high risk for resistance development, or the absence of effective alternative control methods that could contribute to a reduction of selection pressure.…”
Section: Discussionmentioning
confidence: 99%
“…Such problems have been faced in the past in B. cinerea populations that have developed resistance worldwide to all site-specific fungicides, associated with target site modifications due to mutations’ presence in genes encoding the target site of the fungicides ( Brent and Hollomon, 2007 ; Hahn, 2014 ; Fernandez-Ortuno et al., 2017 ; Fillinger and Walker, 2016 ; Shao et al., 2021 ). More recent studies have shown that in pathogen populations throughout the world, strains have been selected possessing more than one target-site alternation conferring resistance to the respective fungicides and leading to multiple resistance (MLR) to fungicides ( de Miccolis Angelini et al., 2014 ; Rupp et al., 2017 ; Naegele et al., 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…It has been ranked as a high-risk plant pathogen in developing fungicide resistance . In fact, B. cinerea populations resistant to single-site inhibitors or to multiple fungicides with different modes of action have been reported throughout the world. , More seriously, public concerns have been rising promptly for the negative effects posed by conventional fungicides on humans and the environment …”
Section: Introductionmentioning
confidence: 99%